Teori Kedaulatan Negara - David Doresta Wijaya; Nurul Mubin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Sovereignty is simply the highest power. One of the principles of sovereignty means managing domestic affairs without interference from other countries, this is because the state has power. However, the issue of who owns the power is still a polemic to this day. This is because if something is said to be sovereign but can still be subject to other powers, then that is not sovereignty. Therefore, the emergence of theories of sovereignty did not coincide but developed according to the times, followed by the emergence of philosophers who were more critical about sovereignty in the state. Among the theories is the theory of state sovereignty, which means that the highest power is held by the state. However, as has been explained, this theory still has advantages and disadvantages, which means that the state can be subject to many things, but the state can also be subject to other things.